ANALISA PERAN FIELD STUDY (PRAKTIK MENGAJAR) DALAM MENINGKATKAN KOMPETENSI MENGAJAR MAHASISWAMEGISITER MPI UIN SUNAN KALIJAGA - Andi Mihrajuddin; Khizbullah, Muhammad Amin; Santosa, Sedya; Jannana, Nora Saiva (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
To become an individual figure as expected, the teacher should always improve the quality of himself. Because to produce a quality generation, of course it must be preceded by the creation of quality teachers as well. The professional abilities of teachers must be improved both by the teachers themselves, as well as by other parties who are related and have a relationship, either directly or indirectly. And this was done at UIN Sunanan Kalijaga Yogyakarta for MPI master students with a field study program. This study aims to analyze how the analysis of the role of field study (teaching practice) in improving the teaching competence of megisiter students at MPI UIN Sunan Kalijaga by using a qualitative approach with descriptive research type. The respondents are MPI Masters students at UIN Sunan Kalijaga who practice teaching. by using observation techniques, and interviews. Furthermore, data reduction and presentation are carried out, then conclusions are drawn. The results of the analysis show that the field of study has a very important role in improving students' teaching competence. This is evidenced by the stages carried out, namely preparation, implementation and evaluation of the learning carried out.